2017
DOI: 10.1017/s0922156516000753
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Hate Speech Acts as Incitement to Genocide in International Criminal Law

Abstract: In this article, I argue that we need a better understanding of the theoretical underpinnings of the current debates in international law surrounding hate speech and inchoate crimes. I construct a theoretical basis for speech acts as incitement to genocide, distinguishing these speech acts from speech as genocide and speech denying genocide by integrating international law with concepts drawn from speech act theory and moral philosophy. I use the case drawn on by many commentators in this area of international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Human rights frameworks provide a foundation for basic rights and protections that is an important counterpoint to the false dichotomies between freedom of speech and protection from abuse promoted by libertarian logics. Human rights prohibitions against discrimination, hate speech, and incitement to violence make clear that rights to freedom of expression and conduct carry associated responsibilities not to impinge on the rights of others (Fyfe, ). These are challenges that human rights discourse and law have had to deal with, and there is a large body of existing knowledge that emphasizes context‐specific analysis and proportionate responses to resolve real conflicts between rights where necessary.…”
Section: Gender‐based Violence and Human Rightsmentioning
confidence: 99%
“…Human rights frameworks provide a foundation for basic rights and protections that is an important counterpoint to the false dichotomies between freedom of speech and protection from abuse promoted by libertarian logics. Human rights prohibitions against discrimination, hate speech, and incitement to violence make clear that rights to freedom of expression and conduct carry associated responsibilities not to impinge on the rights of others (Fyfe, ). These are challenges that human rights discourse and law have had to deal with, and there is a large body of existing knowledge that emphasizes context‐specific analysis and proportionate responses to resolve real conflicts between rights where necessary.…”
Section: Gender‐based Violence and Human Rightsmentioning
confidence: 99%
“…It is a speech that verbally attacks a person or a group of persons because of different origins, races, gender, sexual orientation, religion, or other criteria. 8 It is known that words can cause many things, and one of the effects is that they can cause significant evil. Words can cause direct psychological harm, but they can also directly or indirectly affect causing physical violence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that hate speech can have a detrimental impact on the targeted individuals or groups, ranging from causing psychological harm (Nielsen, 2002;Maitra, 2012;Boeckmann & Liew, 2002) to inciting violence (Muller & Schwarz, 2018;Fyfe, 2017). Hate speech offends, assaults the dignity, invades the autonomy, creates emotional distress, affects the personal development of the victims, and generally, by disrespecting the cultural diversity, undermines the democratic process (Brown, 2015).…”
Section: Introductionmentioning
confidence: 99%